Exploring an adverse impact of smartphone overuse on academic performance via health issues: a stimulus-organism-response perspective. Issue 7 (19th May 2021) - Fu, Shaoxiong; Chen, Xiaoyu; Zheng, Han
ABSTRACT : While previous research suggests that smartphone overuse relates to users' adverse health issues such as insomnia, nomophobia, and poor eyesight, few studies have explored the mediating role of such health issues in the relationship between smartphone overuse and academic performance. Guided by the Stimulus-Organism-Response (S-O-R) framework, this study develops a model to understand the relationships among students' smartphone overuse, health issues (i.e. insomnia, nomophobia, and poor eyesight), and academic performance. Moreover, we introduce a moderating role of health information literacy in the relationship between smartphone overuse and health issues. To validate the model, we collect representative data through a large-scale field survey at a public university in China. 6, 855 valid responses are retained for data analysis using a structural equation modelling technique. The main results are: (1) health issues – insomnia, nomophobia, and poor eyesight – partially mediate the relationship between smartphone overuse and students' academic performance; (2) health information literacy can moderate the relationship between smartphone overuse and the health issues including insomnia and poor eyesight, while the relationship between smartphone overuse and nomophobia is not affected. Finally, we draw related theoretical and practical implications.